ANALISIS FAKTOR RESIKO KETUBAN PECAH DINI DI PUSKESMAS MARGADANA - Resty Himma Muliani (Jurnal Ilmiah Kebidanan Imelda, 2024)
Maternal Mortality Rate is an indicator of maternal welfare that occurs from pregnancy to the end of the postpartum period. Infection is one of the contributors to AKI in Indonesia. Premature rupture of membranes is a condition where the membranes rupture before the time of delivery which occurs at the end of pregnancy or prematurely which can cause infection. This research is a descriptive study with the research objective to determine the risk factors for KPD in the Margadana Health Center area of ??Tegal City. The total population is 22 respondents. The research results showed that the majority of respondents who experienced premature rupture of membranes were multiparous and aged 20 to 35 years. There were more respondents with normal fetal position than abnormal position and most respondents did not experience pre-eclampsia.